2019
DOI: 10.1029/2019ms001733
|View full text |Cite
|
Sign up to set email alerts
|

Using an Arbitrary Moment Predictor to Investigate the Optimal Choice of Prognostic Moments in Bulk Cloud Microphysics Schemes

Abstract: Most bulk cloud microphysics schemes predict up to three standard properties of hydrometeor size distributions, namely, the mass mixing ratio, number concentration, and reflectivity factor in order of increasing scheme complexity. However, it is unclear whether this combination of properties is optimal for obtaining the best simulation of clouds and precipitation in models. In this study, a bin microphysics scheme has been modified to act like a bulk microphysics scheme. The new scheme can predict an arbitrary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 32 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…An idea that has been suggested recently is that cloud processes may be better represented if different distribution moments were predicted. Igel (2019) found that the mass evolution during collision‐coalescence could be better represented by predicting the 0th, third, and eighth moments of the cloud droplet distribution rather than the 0th, third, and sixth. Different rain moment combinations were not tested.…”
Section: Amp Performancementioning
confidence: 99%
See 4 more Smart Citations
“…An idea that has been suggested recently is that cloud processes may be better represented if different distribution moments were predicted. Igel (2019) found that the mass evolution during collision‐coalescence could be better represented by predicting the 0th, third, and eighth moments of the cloud droplet distribution rather than the 0th, third, and sixth. Different rain moment combinations were not tested.…”
Section: Amp Performancementioning
confidence: 99%
“…This study makes use of the Arbitrary Moment Predictor (AMP) which was first described in Igel (2019). AMP uses the cloud microphysical parameterizations of the Hebrew University spectral bin model (Khain et al., 2004).…”
Section: Amp Descriptionmentioning
confidence: 99%
See 3 more Smart Citations